On the fracture mechanisms of nacre: Effects of structural orientation. (11th November 2019) - Jiao, D.; Qu, R.T.; Weng, Z.Y.; Liu, Z.Q.; Zhang, Z.F.
Abstract: The nacre of mollusk shells is distinguished by an exceptional mechanical efficiency which is derived essentially from its lamellar structure and frequently acts as a source of inspiration for the development of biomimetic materials. The structure and mechanical properties of nacre have been intensively investigated with a special focus on its toughening strategies; nevertheless, the fracture mechanisms, more specifically the critical stress/strain conditions for the failure of nacre, and the effects of structural orientation and hydration state remain largely unexplored. Here uniaxial compression tests were performed on nacre of both dry and hydrated states with different off-axis angles, i.e., the inclination of loading axis with respect to the lamellar structure, ranging from 0° to 90°. The mechanical properties and fracture characteristics of nacre and their dependences on the structural orientation and hydration state were elucidated in terms of mechanics behind failure. Quantitative relationships were established between the mechanical properties and off-axis angle based on different failure criteria. The competition between the fracture modes of fragmentation and shearing was quantified by comparing their respective driving force and resistance on the interfacial plane. This study may aid the understanding on the mechanical behavior of nacre and nacre-inspired synthetic materials and promote a better replication of the underlying design principles of nacre in man-made systems.